Thioredoxin-interacting protein in diabetic retinal neurodegeneration: A novel potential therapeutic target for diabetic retinopathy - Liu, Chengzhi; Dong, Wenkang; Lv, Zhengshuai; Kong, Li; Ren, Xiang (Frontiers in Neuroscience, 2022)
Diabetic retinopathy (DR) is a common complication of diabetes mellitus and has been considered a microvascular disease for a long time. However, recent evidence suggests that diabetic retinal neurodegeneration (DRN), which manifests as neuronal apoptosis, a decrease in optic nerve axons, and reactive gliosis, occurs prior to retinal microvascular alterations. Thioredoxin-interacting protein (TXNIP) is an endogenous inhibitor of thioredoxin (Trx), and it acts by inhibiting its reducing capacity, thereby promoting cellular oxidative stress. In addition, it participates in regulating multiple signaling pathways as a member of the α-arrestin family of proteins. Accumulating evidence suggests that TXNIP is up-regulated in diabetes， plays a pivotal role in the pathophysiological process of DR. In this review, we summarized the role of TXNIP in DRN, aiming to provide evidence for DR treatment in the future.